College Algebra (6th Edition)

Published by Pearson
ISBN 10: 0-32178-228-3
ISBN 13: 978-0-32178-228-1

Chapter P - Prerequisites: Fundamental Concepts of Algebra - Exercise Set P.3 - Page 49: 113


${x^{3} y^{-2}}$ = $\frac{x^{3}}{y^{2}}$

Work Step by Step

$(\frac{x^{-\frac{5}{4}}y^{\frac{1}{3}}}{x^{-\frac{3}{4}}})^{-6}$ = $({x^{-\frac{5}{4} + \frac{3}{4}} y^{\frac{1}{3}}})^{-6}$ = $({x^{-\frac{2}{4}} y^{\frac{1}{3}}})^{-6}$ = $({x^{-\frac{2}{4}\times-6} y^{\frac{1}{3}\times-6}})$ = ${x^{3} y^{-2}}$ = $\frac{x^{3}}{y^{2}}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.